PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2012-2014 - admin, Muhammad Fadillah Arnas B41112152 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2016)
This study aimed to examine the variables that can affect the capital structure. The variables in question is good corporate governance is proxied by the board of directors, independent directors, institutional ownership, and managerial ownership. The sample in this study is the Sector Consumption Manufacturing Company listed on the Stock Exchange (Stock Exchange Indonesia) in 2012-2014. Data analysis techniques used in this research is multiple regression analysis. The results show that good corporate governance is proxied by the board of directors, independent directors, institutional ownership, and ownership manjerial no significant effect on the capital structure. Therefore, the four variables can not be used as indicators of the company in determining the capital structure. Keywords: good corporate governance, the board of directors, independent                             directors, institutional ownership, and managerial ownership